Association between ferritin levels and altitude-dependent cardiorespiratory fitness in mountain guides - Pühringer, Reinhard; Muckenthaler, Martina; Burtscher, Martin (High altitude medicine & biology, 2023)
Pühringer, Reinhard, Martina Muckenthaler, and Martin Burtscher. Association between ferritin levels and altitude-dependent cardiorespiratory fitness in mountain guides. High Alt Med Biol. 24:139-143, 2023. - Background: Higher ferritin levels may be associated with lower cardiorespiratory fitness (CRF; i.e., maximal oxygen uptake, VO2max) and may represent early markers of cardiovascular risk but may also support high-altitude acclimatization. To evaluate these potential associations, data recordings from a large sample of male mountain guides have been analyzed. - Methods: A total of 154 data sets (including anthropometric data, VO2max, blood lipids, hemoglobin, ferritin, and transferrin levels) of regularly physically active and well-acclimatized mountain guides were available for analyses. Participants performed equal incremental cycle ergometer tests to exhaustion at low (600 m) and (∼1 week later) at moderate altitude (2,000 m). - Results: Ferritin levels were positively correlated with levels of hemoglobin (r = 0.29, p < 0.01), total cholesterol (r = 0.18, p < 0.05), triglycerides (r = 0.23, p < 0.01), and low-density lipoprotein (r = 0.22, p < 0.01), and negatively with high-density lipoprotein levels (r = −0.16, p < 0.05) and also with baseline (taken at low altitude) VO2max values (r = −0.19, p < 0.05). In contrast, higher ferritin levels were associated with less VO2max decline from low-to-moderate altitude (r = 0.26, p < 0.01). - Conclusion: Higher ferritin levels in male mountain guides are weakly associated with lower CRF and higher prevalence of cardiovascular risk factors but with slightly less reduction in VO2max when acutely exposed to moderate altitude. The clinical relevance of these observations needs further investigation.
Online veröffentlicht: 16. Juni 2023
Gesehen am 01.10.2024